Manifestasi Kulit pada Pasien COVID-19 - Mega Rukmana Dewi (CV. Jasa Sukses Abadi, 2020)
Corona virus disease 2019 or commonly known as COVID-19 is an infection by acute respiratory virus Coronavirus-2 (SARS-CoV-2). In Indonesia, first cases COVID-19 discovered on March 2, 2020 there are 2 cases. Until June 3, 2020, there were 28,233 confirmed cases with 1,698 deaths. In province of Lampung, there were 136 confirmed cases with 11 cases of death. The most common manifestations in COVID-19 patients is respiratory symptoms. Skin manifestations are rarely found of COVID-19 patients but there is 2 cases reported in China shows skin manifestations. Skin manifestations found of COVID-19 patients in several cases include morbilliform rash, urticaria, rash with ptekie, rash with purpura, papulovesicular lesions, chilblain and livedoid lesions.